Changes in the vaccination rate among healthcare workers in response to hospital policies - Lee, Jin Young; Park, Ji Young; Lee, Young Hee; Kim, Je Hun; Park, Jong Woo (The Journal of Infection in Developing Countries, 2018)
Introduction: Vaccination is the most effective method of preventing infectious disease among healthcare workers (HCWs). Although HCWs are recommended to receive vaccination, the vaccination rates have been low. We sought to investigate the effect of HCWs’ vaccination recommendation program by the types of enforcement and influencing factors on compliance, with the aim of enhancing their immunity. Methodology: First and second interventions were carried out. During the first intervention, vaccinations were recommended through official documents. Hepatitis B vaccination was mandatory. Diphtheria toxoid, acellular pertussis (Tdap) and Hepatitis A vaccinations were recommended without financial support. MMR and varicella vaccinations were recommended with fees for the antibody test were covered by the hospital. One-to-one consultation (OC) regarding vaccination was held in the second intervention. Aside from the OC, the second intervention followed the same procedure as the first intervention for the antibody tests and vaccination, but differed in that pertussis vaccination fees were covered. Results: The immunization rates for infectious diseases were greater after the second intervention than the first intervention. The rate of immunized HCWs with hepatitis B virus was 100% at the end of the second intervention. The greatest increase in immunization rates from the first to the second intervention was that for pertussis, and the second greatest was that for hepatitis A. Age and working units were influencing factors on hepatitis A vaccine compliance. Conclusions: In order to increase vaccination rates, efforts must be made to deliver information to individual HCWs through OC as well as financial support including a mandatory policy.